Lyric poetry : the pain and the pleasure of words - Blasing, Mutlu Konuk, 1944- (Princeton, N.J. : Princeton University Press, 2007)
Lyric poetry has long been regarded as the intensely private, emotional expression of individuals, powerful precisely because it draws readers into personal worlds. But who, exactly, is the "I" in a lyric poem, and how is it created? In Lyric Poetry, Mutlu Blasing argues that the individual in a lyric is only a virtual entity and that lyric poetry takes its power from the public, emotional power of language itself. In the first major new theory of the lyric to be put forward in decades, Blasing proposes that lyric poetry is a public discourse deeply rooted in the mother tongue. She looks to po.
The lyric subject -- The historical "I" -- The scripted "I" -- The body of words -- Four quartets: rhetoric redeemed -- Wallace Stevens and "The less legible meanings of sounds" -- Pound's soundtrack: "Reading Cantos for what is on the page" -- Anne Sexton, "The typo" -- Coda: the haunted house of "Anna."
Includes bibliographical references (pages 205-211) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Lyric poetry -- History and criticism; Poésie lyrique -- Histoire et critique; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; LITERARY CRITICISM -- Poetry; Lyric poetry; Lyric poetry -- History and criticism; Poésie lyrique américaine -- 20e siècle -- Histoire et critique; Criticism, interpretation, etc